Simulation of automatic exciting regulators of synchronous generators in hybrid real-time power system simulator - Borovikov Y. S. Yuri Sergeevich; Sulaymanov A. O. Almaz Omurzakovich; Gusev A. S. Alexander Sergeevich; Andreev M. V. Mikhail Vladimirovich (2014, 2014)
Title screen